Biosynthesized zinc oxide and titanium dioxide nanoparticles by aloe vera extract for tunable Q-switched application - Muhammad, Nur Ainnaa Mardhiah; Awang, Noor Azura; Nik Mahmud, Nik Noor Haryatul Eleena; Zalkepali, Noor Ummi Hazirah Hani; Muhamad Zamri, Ain Zamira; Basri, Hatijah; Rasli, Nurul Izwanie (Elsevier, 2023)
Zinc oxide (ZnO) and titanium dioxide (TiO2) nanoparticles (NPs) were biosynthesized by using aloe vera extract for tunable Q-switched application. ZnO TiO2 NPs was then prepared as a saturable absorber (SA) via mechanical exfoliation technique. By measuring nonlinear optical absorption, the modulation depth and saturation intensity were 1.57 % and 0.05 MW/cm2 , respectively. The obtained output pulse had a 1567.60 nm central wavelength and a signal-to-noise ratio (SNR) of 44.94 dB at a pump power of 248.50 mW. The increase of pump power from 178.00 mW to 248.50 mW has led to continuously increase in the repetition rate from 7.70 kHz to 12.99 kHz and decrease from 45.35 µs to 28.93 µs of pulse width, respectively. At maximum pump power, 5.06 nJ of pulse energy was also recorded. When the tunable bandpass filter (TBF) was incorporated into the cavity, the wavelength-tunable Q-switched pulses was constructed, and the tuning wavelength from 1530 nm to 1570 nm that of 40 nm covering wavelength was attained. This finding suggests that a wider range of tunable and simple designs is applicable to optical communications and sensing applications.